Analysis of genetic characteristics of 436 children with dysplasia and detailed analysis of rare karyotype - Miao Zong-Yu; Chen Shi-Feng; Wu Hong; Liu Xiao-Yan; Shao Hui-Yuan (Open Life Sciences, 2022)
Chromosomal abnormality is one of the important causes of dysplasia in children. However, due to regional and ethnic differences, the reported rates of chromosomal abnormalities in patients with dysplasia vary greatly. Moreover, the clinical manifestations in children with rare chromosomal diseases were heterogeneous. So, we retrospectively analyzed the karyotype results of 436 children with dysplasia and conducted a detailed analysis of rare chromosomal diseases. The results showed that chromosomal abnormalities were present in 181 of 436 cases. Intellectual disability, dysmorphology, congenital malformations, the disorder of sexual development, and short stature were the main five clinical symptoms in children with chromosomal abnormalities. Moreover, 136 cases of Trisomy 21 (Tri21) were detected, of which 130 were standard Tri21, 5 were robertsonian Tri21, and 1 was chimera type. In addition, 16 cases of rare abnormal karyotype, including complex Tri21, complex Turner syndrome, 4p-syndrome, 18q-syndrome, and 5p-syndrome, were also detected. In summary, chromosome abnormality is one of the important causes of dysplasia in children. Furthermore, prenatal screening and diagnosis could play a great significance in preventing dysplasia in children. In addition, the retrospective analysis of rare cases is valuable for clinical diagnosis and risk assessment of recurrence.